Contrasting Life Traits of Sympatric Calanus glacialis and C. finmarchicus in a Warming Arctic Revealed by a Year-Round Study in Isfjorden, Svalbard - Hatlebakk, Maja; Kosobokova, Ksenia; Daase, Malin; Søreide, Janne E. (Frontiers in Marine Science, 2022)
The calanoid copepod Calanus glacialis dominates the mesozooplankton biomass in the Arctic shelf seas, but its smaller North Atlantic sibling Calanus finmarchicus is expanding northwards and may potentially replace it if the climate continues to warm. Here we studied the population structure, overwintering strategies, gonad maturation and egg production of C. glacialis and C. finmarchicus over a period of 15 consecutive months in a high-Arctic fjord with sub-Arctic ocean climate and no sea ice formation in winter. The relative proportions of C. glacialis and C. finmarchicus varied throughout the study period, but with an overall dominance of C. glacialis. The overwintering population of Calanus glacialis was dominated by copepodite stage CIV (74 %) while C. finmarchicus overwintered primarily as CV (65 %), reflecting a primarily two- and one-year life cycle, respectively. Adult males and females of C. glacialis appeared as early as October with a peak during December-January, two months earlier than in C. finmarchicus, with a corresponding one-month earlier peak in recruitment for C. glacialis. While C. glacialis reproduced pre-bloom with egg production peaking during the bloom, C. finmarchicus started egg laying during the bloom and continued to reproduce throughout the summer. Seasonal changes in the population structure suggest that C. finmarchicus born early in spring are able to develop to CV during summer and overwinter successfully, while offspring born later in the season do most likely not reach the CV overwintering stage. The ability to reproduce early and the flexibility to alter between 1- and 2-year life cycles give C. glacialis an advantage over C. finmarchicus in high-Arctic unpredictable environments with short-pulsed primary production regimes. Our data indicate that C. glacialis and C. finmarchicus occupy similar environmental niches, but different timing in reproduction reduces the competition. If sea temperatures remain within their temperature-tolerance ranges, both C. glacialis and C. finmarchicus seem to benefit from warming due to accelerating growth and higher survival of the recruits as long as C. glacialis has access to a colder refuge by descending to deeper depths.